Regional-potential-based plantation vocation education analysis in East Kalimantan Province - Kautsar Eka Wardhana; S. Sukamto (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
This study aims do provide plantation vocation education facilities in accordance with the needs of the plantation labor market for several years to come.This was a quantitative study analyzing secondary data and setting the plantation vocation education needs by first making a projection of the population comprising the age group of 16-18 years in East Kalimantan Province.The research conclusions show: East Kalimantan Province need plantation vocation Education. The projection of plantation workers in East Kalimantan Province for 5 years to come from 2015 to 2019 on the whole experiences an increase in the needs for plantation workers continuously. In relation to the results of the projection for plantation workers in East Kalimantan Province for 5 years to come, the needs for vocational education in plantation in the province increase continuously.